Valorization of fruits and vegetables waste through green extraction of bioactive compounds and their nanoemulsions-based delivery system - Saini, Anuradha; Panesar, Parmjit Singh; Bera, Manab Bandhu (Bioresources and bioprocessing, 2019)
Fruits and vegetables, a significant segment of food sector, generate large volume of wastes annually. They constitute an excellent source of several valuable components (carotenoids, polyphenols, etc.), also known as bioactive compounds. These bioactive compounds have a positive impact on health and are known to modulate the metabolic processes as well as influence the cellular activities in the human health due to their antioxidant, anti-cancer, anti-inflammation, anti-allergenic and anti-atherogenic properties; depending upon the pathway and their bioavailability in the body. Despite this, some of these compounds are hydrophobic in nature and therefore are less bioavailable in the body. However, with the technological advancements like nanoemulsions, their solubility, stability and functional properties can be enhanced. This review provides the comprehensive information about the green extraction techniques and innovative delivery system such as nanoemulsions for bioactive compounds generated from fruits and vegetables waste.